2019
DOI: 10.1002/bmc.4495
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of membrane transport mechanisms of endogenous substrates using chromatographic techniques

Abstract: Membrane transporters are expressed in various bodily tissues and play essential roles in the homeostasis of endogenous substances and the absortion, distribution and/or excretion of xenobiotics. For transporter assays, radioisotope-labeled compounds have been mainly used. However, commercially available radioisotopelabeled compounds are limited in number and relatively expensive. Chromatographic analyses such as high-performance liquid chromatography with ultraviolet absorptiometry and liquid chromatography w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 202 publications
(216 reference statements)
0
3
0
Order By: Relevance
“…Numerous reports are available on potential methods to be used for the determination of DA concentrations, these include spectroscopic, 5,6 chromatographic, 79 and electrochemical sensing. 6,1012 Of these various methods, electrochemical sensing offers rapid, effective and efficient testing with low detection limits. 1315 During the electrochemical oxidation of DA, dopaminoquinone is formed through a one-step two-electron transfer process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports are available on potential methods to be used for the determination of DA concentrations, these include spectroscopic, 5,6 chromatographic, 79 and electrochemical sensing. 6,1012 Of these various methods, electrochemical sensing offers rapid, effective and efficient testing with low detection limits. 1315 During the electrochemical oxidation of DA, dopaminoquinone is formed through a one-step two-electron transfer process.…”
Section: Introductionmentioning
confidence: 99%
“…6,1012 Of these various methods, electrochemical sensing offers rapid, effective and efficient testing with low detection limits. 1315 During the electrochemical oxidation of DA, dopaminoquinone is formed through a one-step two-electron transfer process. 16 This process, however, this is not reproducible on bare electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…OATP4C1 is the only member of the OATP family expressed in the kidneys. It localizes to the basolateral membrane of the renal proximal tubular cells and is involved in the excretion of thyroid hormone [ 29 ], cyclic adenosine monophosphate [ 29 ], uremic toxins [ 30 , 31 , 32 , 33 ], cardiac glycosides (ouabain and digoxin) [ 29 , 34 , 35 ], methotrexate [ 29 ], and sitagliptin [ 36 ] into the urine. We have previously shown that 10 drugs, namely, nicardipine, spironolactone, fluvastatin, crizotinib, levofloxacin, clarithromycin, ritonavir, saquinavir, quinidine, and verapamil, strongly inhibited OATP4C1 [ 37 ].…”
Section: Introductionmentioning
confidence: 99%